An overview of R & D activities on gravity, low-pressure and lost foam casting of magnesium-base alloys at CANMET-MTL - J. P. Thomson (Canadian Institute of Mining, Metallurgy and Petroleum, 2004)
Magnesium alloys are steadily improving their market share as structural components especially in the transportation sector. Therefore, there is a great deal of interest from the automotive and the metal casting industry to develop viable economic casting processes for magnesium-base alloys. This paper summarizes the preliminary results on the continuing projects within CANMET-MTL on casting processes such as gravity and low-pressure casting in sand molds, permanent molds and lost foam.